Peningkatan Pemberdayaan Masyarakat melalui CSR PLN Mencapai Kesadaran Lingkungan Sejak Dini - Lintang Laxita Chandra Dewi; Rahmawati Rahmawati; Buffon Yoppy Trie Ambodo; Muhammad Fadly Miftaqul Amirullah (International Forum of Researchers and Lecturers, 2024)
Improving community welfare is the main goal, of course, and one of the main goals of CSR. Companies can help and improve communities in social, cultural, economic, and physical areas by carrying out corporate social responsibility. By doing so, they can make the community feel helped in improving their welfare If someone offers them help, they tend to see it positively because it is evidence of gratitude and empathy shown. The use of appropriate theories to study community empowerment and capacity building of the River School, including community empowerment through CSR programs, River Schools as a model of environmental education, the role of PLN CSR in environmental education at River Schools, early environmental awareness through CSR and River Schools, the impact of CSR programs on community empowerment and independence. This study uses a qualitative approach with a case study of community empowerment through PLN CSR to explore early environmental awareness The location of this research was carried out in Gunung Anyar Tambak Village Rt.01 Rw.01 Surabaya, which is an area used by Bank Sampah by PT. PLN (Persero). The PLN CSR program involving various parties in environmental education has a positive impact on shaping the mindset of the community who are more concerned about environmental sustainability. Awareness built early on, especially in children and adolescents, is expected to produce a generation that is more responsive to environmental issues. Counseling involving schools in this sub-district has proven effective in building a deeper understanding, which can then be passed on to their families. Therefore, it is important for PLN to continue to assist the community, provide adequate facilities and infrastructure, and provide incentives or awards for those who succeed in protecting the environment and managing resources wisely.